The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1365-4632.2005.02504.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial: Pioglitazone versus placebo in patients with plaque psoriasis (the P6)

Abstract: This is the first report from a controlled trial demonstrating that pioglitazone could be considered as an efficacious and safe agent for the treatment of plaque psoriasis. The optimum dose and duration of pioglitazone therapy remain to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 40 publications
1
57
0
2
Order By: Relevance
“…However, their clinical efficacy needs evaluation as PPARb/d agonist, tetradecylthioacetic acid, did not exhibit beneficial effects when applied topically on psoriasis plaques in a pilot study [46]. Shafiq et al [79] in a double-blind clinical trial evaluated 70 patients Arch Dermatol Res with moderate to severe psoriasis who were given placebo, 15 mg/day of pioglitazone or 30 mg/day of pioglitazone. At the end of 10-week trial, PASI scores improved significantly in treated patients with greater benefit in those receiving higher doses of pioglitazone.…”
Section: Psoriasismentioning
confidence: 99%
“…However, their clinical efficacy needs evaluation as PPARb/d agonist, tetradecylthioacetic acid, did not exhibit beneficial effects when applied topically on psoriasis plaques in a pilot study [46]. Shafiq et al [79] in a double-blind clinical trial evaluated 70 patients Arch Dermatol Res with moderate to severe psoriasis who were given placebo, 15 mg/day of pioglitazone or 30 mg/day of pioglitazone. At the end of 10-week trial, PASI scores improved significantly in treated patients with greater benefit in those receiving higher doses of pioglitazone.…”
Section: Psoriasismentioning
confidence: 99%
“…A striking improvement of skin lesions had initially been documented in patients with psoriasis treated with the oral PPARg activator troglitazone (9,113). Although subsequent clinical trials using the oral PPARg activator rosiglitazone did not substantiate the initial troglitazone observation (114), favorable effects of oral pioglitazone not only on psoriatic skin lesions (10,115) but also on psoriatic arthritis (8) have been reported. An ongoing phase II trial is currently evaluating the efficacy and safety of a combination of pioglitazone with acitretin in psoriasis (NCT00395941: clinicaltrials.gov).…”
Section: Clinical Trials In Humansmentioning
confidence: 99%
“…14,[16][17][18] Further evidence in support of a role for Thiazolidinediones in the treatment of psoriasis was provided Brauchli et al who found a statistically significant decrease in the risk for the development of psoriasis in long-term users of TZDs compared with nonusers. 19 Considering the fact that the effect of TZDs is largely through inhibition of epidermal cells and Methotrexate by suppression of lymphoid cells, and since psoriasis is a disease of both epidermal and lymphoid cells, there is a strong theoretical possibility that these two agents could act synergistically.…”
Section: Introductionmentioning
confidence: 99%